The Difference between Business Process Management, System Analysis and Other Types of Business Process Modeling - El-sharif, Israr Abd Al-karim (Journal of Economic, Administrative and Legal Sciences, 2017)
This article trying to lay emphasis on four types of business modeling evergreen topics: business processing management, business analyzing, system analyzing and business processing reengineering by doing comparison between them. The conceptual foundation of the research is based on insights from the resource-based view (RBV) papers, books and theory its complementary competence perspective; the literature; and from the findings of the exploratory study. The research methodology used for descriptive research design. A major element of the paper is offers a number of an original contribution to students, academics and practitioners. The paper is valuable for them because its development and validation of the research model and its accompanying measurement instrument. The findings show these concepts are important and required to work closely together in order to deliver a set of included small business services to the user community, otherwise the overall technology services themselves will not provide any value to the business unless data should be used to achieve the requirements. It is evidently that combination of these concepts and Information Technologies (IT) results into reliable systems in the enterprises. The Business Processing management, The Business analyzing, both system analyzing and Business Processing Re-engineering can be considered as complementary to each other rather than as a substitute like piece of puzzle. They are contributing to the value addition of the small business.